Massive blood transfusion in relation to delivery: incidence, trends and risk factors: a population‐based cohort study. (23rd September 2019) - Thurn, L; Wikman, A; Westgren, M; Lindqvist, PG
Abstract : Objective: To estimate incidence, trends over time, and risk factors for massive blood transfusions in obstetric patients. A secondary aim was to evaluate transfusion ratios in relation to massive transfusion. Design: Population‐based cohort. Setting: Five hospitals, in the Stockholm County, Sweden, from 1990 to 2011. Population: All women that gave birth in Stockholm county, Sweden, and who received blood transfusions postpartum between 1990 and 2011. Methods: Data on pregnancies and deliveries from the Swedish National Medical Birth Registry was cross‐linked to the Stockholm transfusion database. Massive blood transfusion was defined as the transfusion of ≥10 units of red blood cells from partus through the next day. Main outcome measures: Main primary outcome was massive blood transfusion postpartum. Results: Our cohort comprised 517 874 deliveries. Massive blood transfusion occurred in 277 women, for an incidence of 5.3 per 10 000 deliveries, and increased by 30% ( P  <   0.001) between the first and the second half of the study period. Major risk factors apparent before delivery were abnormal placentation (odds ratio [OR] 41; 95% CI 29.3–58.1), pre‐eclampsia/placental abruption (OR 4; 95% CI 2.8–5.6), and previous caesarean delivery (OR 4; 95% CI 3.1–6.0). Risk factors at time of delivery were uterine rupture, atonic uterus, and caesarean delivery (OR 38, 17, and 3, respectively). Conclusion: We found an increasing trend in the postpartum rate of massive transfusion. Women with abnormal placentation were found to have the highest increased risk. Improved antenatal awareness of these women at risk might improve management and reduce the rate of massive transfusion. Tweetable abstract: Risk of massive blood transfusion in obstetric patients increases with placental complications and prior caesarean section. Tweetable abstract: Risk of massive blood transfusion in obstetric patients increases with placental complications and prior caesarean section.